Transparency by Chinese cities reduces pollution violations and improves air quality - Mengdi Liu; Mark T. Buntaine; Sarah E. Anderson; Bing Zhang (Proceedings of the National Academy of Sciences, 2025)
We provide national-scale experimental evidence from China showing that transparency by local governments improves the management of air pollution. Governments that perform better have more reasons to be transparent, making the causal relationship between transparency and policy outcomes difficult to disentangle. In 2015, we randomly assigned municipal governments in China to a high-visibility, public rating of their adherence to national requirements for transparency about their regulation of pollution. By 2016, this treatment significantly boosted transparency in treated cities relative to control cities, allowing us to observe the effect of randomly increasing transparency in the years that followed. Subsequently, high-polluting firms in treated cities cut their violations by 37% compared to similar firms in control cities. Inspections by local governments increased by about 90% in treated cities relative to control cities. Ambient air pollution decreased between 8 and 10% in treated cities relative to control cities, which likely generated significant health benefits. This study provides strong evidence that governmental transparency causes improved environmental quality, at least in a setting where the public and higher governments want to hold local governments accountable.